Repeat stent implementation for recanalization of the proximal right coronary artery: a case report - Wang, Yabin (J Med Case Rep, 2018)
BACKGROUND: A stent in a false lumen is a common cause of stent occlusion after coronary percutaneous coronary artery intervention therapy, particularly in the culprit lesion of acute myocardial infarction. Here, we present an unusual case of successful recanalization of the proximal right coronary artery with implementation of another stent to crush the previous stent in the false lumen. CASE PRESENTATION: A 40-year-old Chinese man underwent coronary stent implementation in the proximal right coronary artery due to acute inferior wall myocardial infarction at another hospital. Six months later, he underwent coronary angiography re-examination for recurrent symptomatic angina at our hospital. Coronary angiography and intravascular ultrasound confirmed that the previous stent was deployed in the false lumen of the right coronary artery. Then, intravascular ultrasound was used to guide the wire to re-enter the true lumen of the proximal right coronary artery, and another stent was deployed into the true lumen to crush the previous stent. CONCLUSION: Intravascular ultrasound proved to be a pivotal tool in confirming false or true lumen, as well as determining favorable proximal site entry points to avoid rewiring the mesh of the previous stent.